RELATIONSHIP BETWEEN SUPPLIER RELATIONSHIP MANAGEMENT AND IMPLEMENTATION LEVEL OF PUBLIC PROCUREMENT REGULATORY FRAMEWORK IN THE DEVOLVED GOVERNMENTS IN KENYA - Matunga, Denish Ateto; Ngugi, Patrick Karanja; Odhiambo, Romanous (Machakos University Press, 2021)
Purpose: The purpose of this study was to establish the relationship between supplier relationship management and implementation level of public procurement regulatory framework in the devolved governments in Kenya. Methodology: The study adopted census because of the small size of the population. A structured questionnaire was used as a data collection tool. The study also undertook a pilot test on the instrument’s reliability and validity in the 3 counties; Nyamira, Kisii, Homa-Bay Counties where nine (9) respondents were engaged in the pilot study. The use of descriptive and inferential statistics for data analysis was considered. Study engaged the key informers from the 44 county Governments who positively responded hence achieving 100% response rate. The statistical tests were also done in the study. Presentation of data was in form of charts and tables as deemed appropriate. Results: The findings obtained indicated that there was significant relationship between supplier relationship management on level of implementation of public procurement regulatory framework in the devolved governments in Kenya. The findings were found to be positively significant as the p-values 0.00000 which were less than 0.05. The findings indicated that for every unit of supplier relationship management the value of implementation level of public procurement regulatory framework in the devolved governments in Kenya changes with a positive significance increase of 1.105 in the presence of a moderator. Unique contribution to theory, practice and policy: The study recommended that the devolved governments functions should embrace supplier’s commitment level on quality of goods and services in their operations such as information sharing between the buyer, improve on their commitment on suppliers’ payment, increase commitment level in supplier partnership and development to improve the supplier’s commitment level and value addition or creation in service delivery.
Keywords: Supplier Relationship Management; Public Procurement; Regulatory Framework Devolved Governments